Fiscal and institutional factors and taxpayer culture as explanations for the 2018 VAT increase in South Africa - Pearson, Kirsten Susan (Department of Sociology, 2022)
The 2018 Value Added Tax (VAT) rate increase in South Africa is a significant event in that it was the first time since the advent of democracy in South Africa (1994) that the VAT rate had been raised. Located within the discipline of fiscal sociology, this study emphasises the developmental implications of fiscal policy choices. It problematises tax revenue mobilisation to meet growing spending requirements in South Africa. It looks at why, of the various fiscal and tax policy options available, the decision was made to raise the VAT rate. The mixed methods study provides a content analysis of literature obtained through a desk review and statistical analysis of a public opinion survey. By examining the underlying dynamics that influence fiscal policy decisions, it explains how fiscal and institutional factors and taxpayer culture interacted to bring about the decision to increase the VAT rate. It finds that policy decisions with large spending requirements can have an impact on fiscal policy decisions with implications for rights realisation. A conceptual framework specific to the South African context was developed as an output. Additionally, a revised conceptual framework for the determination of taxation was produced.